Legal Challenges in Combating Deepfake Abuse: A Comparative Study of AI Regulation in Privacy Protection and Digital Security - Muhammad Doing; Yuko Fitrian; Sy Muhammad Ridho Rizki Maulufi Alkadrie; W Warriyodi; Muhammad Reza Fahlevi; A Aprieyanti (Proceeding International Conference Restructuring and Transforming Law, 2025)
Deepfake technology is an artificial intelligence (AI)-based technology that is rapidly evolving but also poses risks of identity fraud, misinformation dissemination, and privacy violations. This study analyzes the legal challenges in addressing the misuse of deepfake technology in Indonesia and compares them with international regulations, such as the European Union's GDPR and AI Act. Using a normative and comparative legal approach, this study finds that Indonesia's Personal Data Protection Law (UU PDP) and Electronic Information and Transactions Law (UU ITE) still have weaknesses in addressing deepfake issues, particularly regarding the lack of clear legal definitions, weak law enforcement, and the absence of digital platform liability. As a solution, this study proposes modifications to regulatory theory by adapting the concepts of the right to be forgotten, AI forensics, and intermediary liability to strengthen Indonesia's legal policies.